LETTERS OF PAYMENTS APPLICATION SYSTEM USING RAD STUDIO XE2 (Case Study : BANDUNG PUBLIC WORKS DEPARTMENT) - Taryanto, Ardi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2017)
Purpose - Developing letter of payment (SPM) Information System in the Program and Financial Subdivision of Bandung Public Works Department by automating the SPM numbering process in one database for easy, fast and accurate data access. Findings - Some of the problems that occur are the duplication or double SPM numbering data, relatively longer data retrieval, and file accumulation that affecting data security risks. Methodology - The steps taken by the survey is the observation of the object to be analyzed. System Analysis by collecting data based on observation, interview, and literature study, and then, program design. After that, the evaluation stage was done to see if the program design is running as expected or not. Testing and Realization - Design and realization through the overall testing of the application program can assist employee performance. The concept of desktop-based application programs using mysql database and using Embarcadero RAD Studio XE2. The design of the system is using local network and wifi because the application system is able to run across all types of existing operating system where there is a server application to run on the client side, making it easier access and maintained as a whole.